Philanthropic Behaviour of Quebecers - Zhao, Wenzhuo (Université d'Ottawa | University of Ottawa, 2015)
Residents of Quebec give less, on average, than those in all other provinces. They also volunteer, on average, the least when compared to time donated in other provinces. Why? This paper empirically examines and compares the giving and volunteering behaviour of Quebecers to that of other Canadians, with the aim of addressing this question. The most recent General Social Survey - Giving Volunteering and Participation (GSS GVP 2013) and Tobit procedure are employed to conduct the analysis. I find that once I control for demographic and socio-economic characteristics, Quebecers behave similarly to others when it comes to money and time donations, except for total volunteering hours. The key factors that seem to explain why the average giving is so much lower in Quebec are that they have the lowest proportion of religious individuals across provinces and that they are in the lower half of low disposable household income when comparing across provinces.